2022
DOI: 10.1080/10640266.2022.2069315
|View full text |Cite
|
Sign up to set email alerts
|

Promising effect of multi-family therapy on BMI, eating disorders and perceived family functioning in adolescent anorexia nervosa: an uncontrolled longitudinal study

Abstract: Safety of the Food Chain and Environment and the MIATA parents' association. We would like to thank as well the Centre Thérapeutique du Trouble alimentaire de l'Adolescent's team for the data collection, especially Nathalie Javaux, Cécile Lemoine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Family functioning was measured with the Family Assessment Device (FAD) [ 20 ] or the Family Adaptability and Cohesion Evaluation Scales (FACES III) [ 21 ]. Overall, two uncontrolled studies found overall improvement in family functioning [ 4 , 22 ], two RCTs [ 19 , 23 ] and one uncontrolled study [ 24 , 25 ] found no change in family functioning. None of the studies found an overall deterioration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family functioning was measured with the Family Assessment Device (FAD) [ 20 ] or the Family Adaptability and Cohesion Evaluation Scales (FACES III) [ 21 ]. Overall, two uncontrolled studies found overall improvement in family functioning [ 4 , 22 ], two RCTs [ 19 , 23 ] and one uncontrolled study [ 24 , 25 ] found no change in family functioning. None of the studies found an overall deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of readability, this article does not distinguish between these two versions. Furthermore, other variations such as multifamily therapy (MFT) [ 4 ] and parent-only therapy [ 5 ] have been developed. All versions and variations have parents in charge of refeeding as the central component.…”
Section: Introductionmentioning
confidence: 99%
“…I.e. that improvements in ED psychopathology, weight and emotion regulation achieved during treatment are generally maintained or improved at follow-up [ 20 , 22 , 53 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Terache and colleagues (2022) also found significant improvements in ED psychopathology and weight increase. The improvements were maintained at 6- and 12-month follow-ups [ 22 ]. Thus, the somewhat limited literature of outpatient MFT for adolescents shows improvements in ED symptomatology, weight, depression, and global outcome after MFT, with some benefit of MFT over other treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The current program (Simic et al, 2022) offers 10 days of MFT alongside single‐FT sessions, as needed, over 6–9 months. Existing evidence suggests that ED‐focused MFT models obtain high levels of satisfaction from participating families, can lead to better outcomes than single FT for adolescents treated in outpatient settings, can improve family functioning and tend to be more cost‐effective (Eisler et al, 2016; Gabel et al, 2014; Terache et al, 2022).…”
Section: Introductionmentioning
confidence: 99%